Why is the topic of the biological embedding of experiences important for translation?. (3rd October 2016) - Rutter, Michael
Abstract: Translational research focuses on innovation in healthcare settings, but this is a two-way process that may have implications for either treatment or prevention. Smoking and lung cancer and the fetal alcohol syndrome are used as examples. Experimental medicine that budges basic and clinical science often constitutes a key way forward. Areas of scientific progress and challenge are discussed in relation to drug action, social cognition, cognitive neuroscience, molecular genetics, gene–environment interaction, and epigenetics. Key concepts and challenges in relation to stress include toxicity, allostatic load, the hypothalamus–pituitary–adrenal axis, and objectives versus subjective stress. The reasons for the need to test causal inferences are discussed. Various kinds of "natural experiments" are discussed in illustration using the assisted conception design, the discordant monozygotic twin design, and the study of universal exposure. Animal models are discussed in relation to enrichment and deprivation effects and the effects of infant separation experiences, epigenetic effects, and the biological embedding of experiences. Translational issues are discussed in relation to the hypothalamic–pituitary–adrenal axis, epigenetics, and inflammation. In conclusion, it is suggested that there are immediate possibilities for experimental medicine but caution is needed with respect to moving into translation too quickly.